2021
DOI: 10.29040/ijebar.v5i1.2092
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Succession in a Family Business: Case Study on Batik Industry in Indonesia

Abstract: The purpose of this study is; To describe succession planning and an effective succession model, to create a successful successor, to describe the planning and design an effective succession model, and to create a successful successor in both PT. Danliris and Batik Semar. The method used in this study is qualitative descriptive. Data collection is by observation and using in-depth interviews. Informant selection was determined by purposive sampling. The validity of the data was tested by the source tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The first cluster (red color) is IBS in connecting with the financing scheme and countries, using such keywords as sustainability, Islamic bank, microfinance, green banking, Pakistan and Malaysia. Research of financing schemes related to IBS on microfinance trends such as Islamic banking in microfinance initiatives (Dusuki, 2008a), profit sharing patterns for microfinance (Darmansyah et al, 2013), Islamic moral transaction mode as a moderator in sustainable Islamic microfinance banks (Aliyu et al, 2017), financial performance of Islamic microfinance (Ibrahim et al, 2018), microfinance as a tool for alleviating poverty (Fitriasari and Dalimunthe, 2019;Tamanni and Besar, 2019) and financing risk of microfinance relates to cyclical to economic conditions (Mohamed et al, 2021). Green banking research trends include shariah compliance of green banking policies (Julia et al, 2016), green banking operations (Kunhibava et al, 2018), green banking performance based on Maqashid al Shariah (Julia and Kassim, 2020) and green banking behaviors (Ali et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first cluster (red color) is IBS in connecting with the financing scheme and countries, using such keywords as sustainability, Islamic bank, microfinance, green banking, Pakistan and Malaysia. Research of financing schemes related to IBS on microfinance trends such as Islamic banking in microfinance initiatives (Dusuki, 2008a), profit sharing patterns for microfinance (Darmansyah et al, 2013), Islamic moral transaction mode as a moderator in sustainable Islamic microfinance banks (Aliyu et al, 2017), financial performance of Islamic microfinance (Ibrahim et al, 2018), microfinance as a tool for alleviating poverty (Fitriasari and Dalimunthe, 2019;Tamanni and Besar, 2019) and financing risk of microfinance relates to cyclical to economic conditions (Mohamed et al, 2021). Green banking research trends include shariah compliance of green banking policies (Julia et al, 2016), green banking operations (Kunhibava et al, 2018), green banking performance based on Maqashid al Shariah (Julia and Kassim, 2020) and green banking behaviors (Ali et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Sustainability impact to financial/firm performance (Jan et al, 2019a(Jan et al, , 2019b(Jan et al, , 2019c, (Jan et al, 2019a), (Nofianti, 2019), (Majeed and Zainab, 2021), (Ismail et al, 2022), (Budiman et al, 2022), (Osmanovic et al, 2022) Bankruptcy prediction (Jan et al, 2019c), (Mehreen et al, 2020) Sustainability factors/ dimensions (Jan et al, 2019a), (Aisjah et al, 2022) SDGs (Saleem et al, 2021), (Jan et al, 2021a(Jan et al, , 2021b) ESG score (Paltrinieri et al, 2020) Dual banking system (Karim et al, 2019), (Alam et al, 2020) Sustainability practices Green banking (Julia and Kassim, 2020), (Q. Ali et al, 2020) Firm strategy and the role of sustainability (Kunhibava et al, 2018), (Abdulahanaa, 2020), (Alketbi et al, 2022), (Jan et al, 2022a(Jan et al, , 2022b) Consumer price (Hossain, 2014) Microfinance (Dusuki, 2008a), (Darmansyah et al, 2013), (Ibrahim et al, 2018), (Fitriasari and Dalimunthe, 2019), (Mohamed et al, 2021), (Tamanni and Besar, 2019) Socio-economic development (Pratiwi, 2016) Human resources, knowledge sharing and innovation (Abbas et al, 2019), (Siswanti and Sukoharsono, 2019), (Janon et al, 2019), (Umar et al, 2021), (Muhammad and Nugraheni, 2022) Ban...…”
Section: Sustainability Measurementmentioning
confidence: 99%
“…The literature on Indonesia's family businesses found that sociocultural and political dynamics are closely related to the development and implementation of family businesses. The local indigenous and Chinese values interact, enriching how the businesses manage the business and succession processes (Istiatin and Susanti, 2021). Preparing their successors by equipping them with an international standard of a foreign educational system is also chosen by many parents to enhance the capability of their children in running the business (Tan et al, 2019).…”
Section: Belowmentioning
confidence: 99%
“…Family business could fail because more often, the family business as a business entity did not make enough innovation decision needed to ensure their unique selling points in this ever-changing world (Danco, 1980 as cited in Istiatin & Susanti, 2021). According to Ward (1997as cited in Miller, 2014, a business that does not do risktaking innovation, would likely to lower their business prospects.…”
Section: Growing Family Businessmentioning
confidence: 99%